How did EU membership of Eastern Europe affect student achievement? - Annika B. Bergbauer (Education Economics, 2019)
The accession of Eastern European countries to the European Union increased family wealth and the returns to schooling. I analyze the change in student achievement due to the EU accession of Eastern Europe building on a panel of six PISA waves covering more than 1 million students in 32 countries. Using a difference-in-differences approach, I find a positive and statistically significant link of EU membership to reading scores by one tenth of a standard deviation. The effect seems robust to including controls from the human capital production function.
Keywords: I28; H52; L15; D82; P5; 330; European Union; student achievement; PISA